Global Capitalism : Its Fall and Rise in the Twentieth Century - Frieden, Jeffry A. (New York W.W. Norton & Company, 2006)
International trade at unprecedented levels, millions of people migrating yearly in search of jobs, the world's economies more open to one another than ever before--such was the global economy in 1900. Then as now, many people considered globalization to be inevitable and irreversible. Yet the entire edifice collapsed in a few months in 1914. Globalization is a choice, not a fact--a result of policy decisions and the politics that shape them. Political scientist Frieden's history explores the golden age of globalization during the early years of the twentieth century, its swift collapse in the crises of 1914-45, the divisions of the Cold War world, and the turn again toward global integration at the end of the century. Full of character and event, it deepens our understanding of the century just past and sheds light on our current situation.--From publisher description.
Include Notes, References and Index
Keywords: International economic relations -- History -- 20th century. -- Capitalism -- Globalization--Economic aspects